2021
DOI: 10.7759/cureus.12473
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behavior and Medication Adherence in Schizophrenic Patients

Abstract: Suicide is one of the potential complications in the Schizophrenic patient population. This review article deals with the significance of antipsychotic medication compliance in decreasing suicidal behavior and hospitalizations in Schizophrenic patients. The medication adherence with second-generation antipsychotics (SGA) like clozapine and long-acting injectables (LAIs) like paliperidone is associated with decrease suicidal behavior and all-cause mortality in Schizophrenic patients. Concomitant treatment of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…This is especially important for schizophrenia treatment, as it has been reported that up to 75% of patients discontinue the treatment within the first year and a half [ 44 ]. Non-adherence to treatment has an enormous impact for this patient as it increases the risk of relapse, hospitalization, and even suicide rates [ 45 , 46 , 47 , 48 , 49 ]. Moreover, there is an obvious economic impact for healthcare systems.…”
Section: Resultsmentioning
confidence: 99%
“…This is especially important for schizophrenia treatment, as it has been reported that up to 75% of patients discontinue the treatment within the first year and a half [ 44 ]. Non-adherence to treatment has an enormous impact for this patient as it increases the risk of relapse, hospitalization, and even suicide rates [ 45 , 46 , 47 , 48 , 49 ]. Moreover, there is an obvious economic impact for healthcare systems.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the ABILIFY MYCITE System is a drug-device combination product (aripiprazole tablets with a sensor) that comprises 4 separate components that enable the monitoring of treatment adherence by a patient and the patient's provider (Table 1). The four components include (1) the ABILIFY MYCITE tablet (DMS tablet), an aripiprazole tablet embedded with an ingestible event marker sensor; (2) MYCITE System patch (DMS patch); (3) MYCITE System smartphone app (DMS app); and (4) MYCITE System dashboard (DMS dashboard).…”
Section: The Abilify Mycite Systemmentioning
confidence: 99%
“…Suboptimal medication adherence is a significant problem for patients with serious mental illness (SMI), including those with schizophrenia, bipolar disorder, posttraumatic stress disorder, and major depressive disorder. Suboptimal adherence among these individuals may lead to symptom exacerbation, relapse, and hospital readmissions [1]. Moreover, suboptimal adherence to prescribed psychotropic medication is associated with increased mortality [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major advantage of clozapine in treatment refractory schizophrenia is that it reduces suicidality. 6,7 Sadly, the corollary is that if patients become nonadherent to clozapine, the impulse to self-harm may return. If clozapine has been stockpiled there is a ready source of drug, even moderate overdosage with which will often prove fatal especially in a nontolerant patient.…”
mentioning
confidence: 99%